Key anatomic findings on fetal ultrasound and MRI in the prenatal diagnosis of bladder and cloacal exstrophy. Issue 5 (October 2020) - Weiss, Dana A.; Oliver, Edward R.; Borer, Joseph G.; Kryger, John V.; Roth, Elizabeth B.; Groth, Travis W.; Shukla, Aseem R.; Mitchell, Michael E.; Canning, Douglas A.; Victoria, Teresa
Summary: Introduction: Prenatal determination of bladder exstrophy (BE) or cloacal exstrophy (CE), known also as the omphalocele-exstrophy-imperforate anus-spinal anomaly complex (OEIS), is challenging. Distinguishing between BE and CE is important because children with CE have many more challenges initially and during their lifetime. An accurate diagnosis is critical when counselling expectant parents. We hypothesized that there are key imaging features that can distinguish BE from CE, and that there are areas of diagnostic concordance and discordance between fetal ultrasound (fUS) and fetal MRI (fMRI) among these entities. Materials and methods: We queried a single institutional IRB-approved registry of children with BE and CE to identify those with accessible fetal imaging from 2000 to 2018, and formal interpretations were collected. Two pediatric radiologists performed independent retrospective blinded review of the images. Criteria evaluated included: genitalia, kidneys, bowel appearance, presence of anal dimple, location of insertion of umbilical cord into the abdomen relative to the abdominal wall defect, umbilical vessels, bladder protuberance, presence of omphalocele, and spine/neural cord abnormalities. We evaluated concordance between radiologic interpretations and postnatal diagnosis, as well as between specific findings in the two diagnostic modalities. Results: Twenty-one infants born between 2000 and 2018 with BE or CE had fetal imaging for review: 15 had both fUS and fMRI, 2 had fUS alone, and 4 fMRI alone. There was 100% concordance between fUS and fMRI in evaluating kidneys, presence of anal dimple, location of abdominal insertion of umbilical cord relative to the defect, number of umbilical vessels, and spine abnormalities/level of neural cord termination. The following discrepancies were observed: 1) genitalia and bowel appearance, and bladder protuberance in 1/15 (6.7%); 2) presence of an omphalocele in 2/15 (13.3%). Of the initial radiologic interpretations, 4/17 (23.5%) of fUS and 2/19 (10.5%) of fMRI erroneously were interpreted as on the OEIS spectrum when the post-natal diagnosis was BE. Errors in diagnosis were due to a protuberant bladder plate extending beyond the plane of the abdominal wall with bowel loops posteriorly mimicking an omphalocele. In all of these BE cases, the abdominal wall defect was located inferior to the umbilical cord insertion on the abdominal wall. Conclusion: An everting bladder plate with bowel loops posterior to the plate in classic BE may be misdiagnosed as CE. Identification of the location of umbilical cord insertion relative to the abdominal wall defect, with fetal US or MRI, results in the correct differentiation between BE and CE. Summary Figure T2 sagittal images of fetal MRI (a&b) and fetal US (c&d) in a patient with BE demonstrating: a&c) insertion of umbilical cord (long arrows) superior to a defect (short arrows), b&d) protuberant bladder plate with bowel posterior to it (short arrows), (in d, abdomen and thorax highlighted by white circle, protuberance outlined in yellow, and umbilical cord highlighted in red) and e) post-natal appearance of male with BE and large protruding bladder. Summary Figure